Reality TV: A Case Study on Viewing Motives of ‘‘Housemates Salone Season Two’’: Array - Conteh, Bilal (Acta Universitatis Danubius. Communicatio, 2021)
Abstract: The study was inspired by the uses and gratification research on reality television and it examines the viewing motives of viewers that watched the famous Sierra Leonean reality TV show ‘Housemates Salone season two’. The study adopted a quantitative research method in the form of a survey questionnaire instrument completed by participants. The results reveal that young people between the ages of 18–24 and 25–34 (students and singles) dominated the show’s viewer demographics, accounting for almost 80% of ‘Housemates Salone season two’ viewership. Findings indicate that 43.6% of viewers watched the show for 3–4 hours daily, while eviction show, Saturday parties and diary room sessions accounted for viewers' most liked aspect of the show. Despite the fact that four motives (entertainment, voyeurism, social interaction, and relaxation) were discovered to be the main motives for watching ‘Housemates Salone season two’, the entertainment motive was discovered to be the most important motive that piqued viewers' interest in watching the show. This study serves as a stepping stone for reality television research in Sierra Leone as it motivates academics and administrators to conduct more studies and invest more in reality entertainment.